Physicochemical properties of stingless bee honey from around the globe: A comprehensive review - Nordin, Abid; Sainik, Nur Qisya Afifah Veronica; Chowdhury, Shiplu Roy; Saim, Aminuddin Bin; Idrus, Ruszymah Bt Hj (Journal of food composition and analysis, 2018)
•Stingless bee honeys do not comply with the quality standards set for Apis mellifera honey.•Compilation of physicochemical data from 522 stingless bee honey samples shows huge variability.•The review suggested the need of a quality standard exclusive for stingless bee honey to be set. Stingless bee honey has been reported to not meet the quality standards set for honey. In response, researchers from Venezuela and Malaysia have proposed unique quality standards for stingless bee honey. The aim of this review is to compile the available data on the physicochemical properties of stingless bee honey already studied from all over the world to propose a harmonized global quality standard for stingless bee. The literature review resulted in the inclusion of 40 studies, assessing 522 honey samples, from 67 different species of stingless bee, habituating 12 countries from all over the world. Taking into account the variety of bee species and the geographical origin for the collection of honey, enormous variability in terms of honey’s moisture content, free acidity, pH, hydroxymethylfurfural content, ash content, electrical conductivity, sugar content, enzyme activity, nitrogen content, soluble solids, minerals composition, phenolic compound, and color were observed. Stingless bee honey possessed greater moisture content, higher acidity, lower sugar composition, and lower enzyme activity in stingless bees compared to Apis mellifera bees. This review justifies the need for a more harmonized standard of this food product, which will include stingless bee honey from around the globe.